Sustainable use of new and recycled materials in coastal and fluvial construction - Masters, Neal (Thomas Telford, 2001)
This manual offers practical guidance on how to apply the principles of sustainable construction in coastal and fluvial construction by assessing the environmental impacts of the alternative project options.